Electromagnetic induction heating of TP-CFRP laminates : FEM modelling and validation - Vankan, W.J.; Hoorn, N. van; Wit, A.J. de; Koenis, T.P.A. (ICAS, 2024)
Accelerated adoption of new and innovative aircraft technologies is necessary to achieve the long-term goals for global aviation towards net-zero carbon emissions by 2050. Many of these innovative technologies are already being investigated. One of these technologies is the application of advanced thermo-plastic (TP) carbon fiber reinforced polymer (CFRP) composite components for light-weight airframe assemblies. The correct implementation of the related innovative material and manufacturing technologies is only possible if accurate predictions of the implications of these technologies can be made. For that purpose, advanced modelling and simulation methodologies are indispensable. For example, the use of advanced 3D finite element method (FEM) modelling is essential for the prediction and understanding of complex local electromagnetic (EM) inductive heating phenomena in composite laminates. Such EM simulations can support induction welding (IW) processes that can be used in the innovative manufacturing and assembly of TP CFRP composite components. This paper presents an efficient modelling and simulation approach for the EM inductive heating of TP CFRP laminates. Besides the EM phenomena in the laminate, also the thermal phenomena including conduction, convection and radiation play a key role in the inductive heating process. Dependencies of the various properties and parameters in the simulations are presented and explained. Moreover, a comparison is made of the simulation results with experimental results.